Prevalence of thrombocytopenia in neonatal sepsis - Chate, Sambhaji; Holikar, Sunil; Nagare, Suyog (Indian Journal of Child Health, 2019)
Background: The problem of neonatal sepsis is enormous in India and many hospital-based studies have revealed an incidence of 30/1000 live births. Objectives: The objectives of this study were to assess the prevalence of thrombocytopenia in culture-positive neonatal sepsis and to observe the outcome of these neonates. Methods: It was a retrospective observational study which was conducted in neonatal intensive care unit (NICU) of a Rural Medical College between September 2018 and December 2018. We have analyzed the records of all the neonates who were admitted at the hospital during this period. We have only included the cases who were culture positive for sepsis and were below 28 days of age. Data were analyzed statistically and p100,000/mm3 was 5.0 days (interquartile range 4.0–7.0). Conclusion: Severe thrombocytopenia was commonly associated with neonatal sepsis. Antibiotics covering these groups of bacteria can be started empirically after collecting the required investigations.